Involvement of epigenetic modification of TERT promoter in response to all-trans retinoic acid in ovarian cancer cell lines - Lorena Losi; Angela Lauriola; Erica Tazzioli; Gaia Gozzi; Letizia Scurani; Domenico D'Arca; Jean Benhattar (BMC, 2019)
Abstract Background All-trans retinoic acid (ATRA) is currently being used to treat hematological malignancies, given the ability to inhibit cell proliferation. This effect seems to be related to epigenetic changes of the TERT (Telomerase Reverse Transcriptase) promoter. When hypomethylated, ATRA-inducible TERT repressors can bind the promoter, repressing transcription of TERT, the rate-limiting component of telomerase. Ovarian carcinomas are heterogeneous tumors characterized by several aberrantly methylated genes among which is TERT. We recently found a hypomethylation of TERT promoter in about one third of serous carcinoma, the most lethal histotype. Our aim was to investigate the potential role of ATRA as an anticancer drug in a sub-group of ovarian carcinoma where the TERT promoter was hypomethylated. Methods The potential antiproliferative and cytotoxic effect of ATRA was investigated in seven serous ovarian carcinoma and one teratocarcinoma cell lines and the results were compared to the methylation status of their TERT promoter. Results The serous ovarian carcinoma cell line OVCAR3, harboring a hypomethylated TERT promoter, was the best and fastest responder. PA1 and SKOV3, two cell lines with an intermediate methylated promoter, revealed a weaker and delayed response. On the contrary, the other 5 cell lines with a highly methylated promoter did not respond to ATRA, indicative of ATRA-resistant cells. Conclusions Our results demonstrate an inverse correlation between the methylation level of TERT promoter and ATRA efficacy in ovarian carcinoma cell lines. Although these results are preliminary, ATRA treatment could become a new powerful, personalized therapy in serous ovarian carcinoma patients, but only in those with tumors harboring a hypomethylated TERT promoter.